How to build cross platform HTML5 games for mobile and web - Freeman, Jesse (O'Reilly Media, 2014)
"Jesse will go into detail on how to build a truly cross platform HTML5 game by using his new Super Paper Monster Smasher Starter Kit which you can play at http://bit.ly/spms-sk-demo. While this webcast talk is geared toward building a Windows 8 HTML5 game, the starter kit contains all the code needed to generate builds for multiple platforms such as the Web, Windows Phone 8, Jesse will also discuss packaging the game up for Chrome Store, FireFox OS as well as using CocoonJS to build native iOS and Android games.All of this is powered by Node, Grunt and ImpactJS. Along the way we will go over how to customize the game engine, it's artwork and discuss ways you can tweak the game play to make it your own. In the end, you will have a complete game which you are free to publish to gain experience on how easy it is to make cross platform HTML5 games."--Resource description page.